Heat Transfer by Transmission in a Zone with a Thermally Activated Building System: An Extension of the ISO 11855 Hourly Calculation Method. Measurement and Simulation - Piotr Michalak (Energies)
Water systems with pipes embedded in the horizontal concrete core slabs can be used for efficient space heating and cooling of passive and low-energy buildings. ISO 11855-4 describes the hourly simulation method of such systems while recommending to use other simulation tools to assess heat flow by transmission to the ambient environment. As it plays an important role in the thermal balance of a conditioned zone, this paper presents two calculation methods to obtain heat flow through the envelope. They were integrated with a general algorithm given in ISO 11855-4 and the simulation tool was developed. To validate the presented solution measurements were performed in a passive office building during the heating (November) and cooling (July) periods. The total heat transfer coefficient by transmission was measured and compared with the theoretical design value. Both proposed simulation algorithms provided results with very good accuracy. In the first period, the mean absolute of percentage error (MAPE) of the indoor air and floor temperatures amounted to 0.65% and 0.75%, respectively. Simulations showed that heating demand was covered mainly by the floor (28.7%), internal gains (21.7%), and ceiling (18.7%), while heat loss to the environment was mainly due to external partitions (94.0%). In the second period MAE and MAPE did not exceed 0.19 °C and 0.90%, respectively. Floor and ceiling were mainly responsible for heat gains removal (61%). Solar radiation was the main source (91%) of internal gains. The results obtained confirmed the assumptions taken. The simulation programme developed does not require the use of additional tools.